The Performing School: The Effects of Market & Accountability Policies - Falabella, Alejandra (Education Policy Analysis Archives, 2014)
Market and accountability educational reforms have proliferated around the globe, along with high expectations of solving countries’ school quality deficits and inequities. In this paper I develop an analytical framework from a critical sociology angle for analyzing the effects of these policies within schools. First I discuss conceptually the configuration of this quasi-market schema and develop the notion of the ‘performing school’. Additionally, I study the effects of these policies within schools, based on a literature review of 130 papers, and focused particularly on a smaller body of critical sociology research (56 papers). The aim is not to produce a comprehensive overview of policy benefits and disadvantages, but to understand school transformations within the current policy scenario. Schools, in this context, are placed within a competition-based schema, where managers and teachers continuously have to compete, marketize and perform ‘successfully’ according to external criterion. These policies are not only changing school practices and triggering 'secondary' effects, but, moreover, they are transforming school life, ethics and teaching profession subjectivities in complex and deeply-rooted ways. In this paper I attempt to challenge policy assumptions and a technocratic view of policy implementation, and invite readers to rethink the nature and consequences of these policy formulae.